2000
DOI: 10.1002/(sici)1097-4547(20000415)60:2<231::aid-jnr12>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

L-cycloserine slows the clinical and pathological course in mice with globoid cell leukodystrophy (twitcher mice)

Abstract: Globoid cell leukodystrophy (Krabbe's disease) is an autosomal recessive disease that affects the lysosomal enzyme galactosylceramidase. Galactosylceramidase removes galactose from galactosylceramide and psychosine, which are derived from sphingosine. In the present study, L-cycloserine (an inhibitor of 3-ketodyhydrosphingosine synthase) was administered to the twitcher mouse, an authentic model of globoid cell leukodystrophy. Twitcher mice treated with L-cycloserine had a significantly longer life span and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 24 publications
1
46
0
Order By: Relevance
“…Because L-cycloserine inhibits the synthesis of sphingosine, it is important to select a treatment regimen that does not completely inhibit the production of sphingosine as it is a key component of cells. Thus, mice did not tolerate doses of L-cycloserine that were much higher than those used in the present study (39).…”
Section: Bone Marrow Transplantation In Twitchersmentioning
confidence: 52%
See 3 more Smart Citations
“…Because L-cycloserine inhibits the synthesis of sphingosine, it is important to select a treatment regimen that does not completely inhibit the production of sphingosine as it is a key component of cells. Thus, mice did not tolerate doses of L-cycloserine that were much higher than those used in the present study (39).…”
Section: Bone Marrow Transplantation In Twitchersmentioning
confidence: 52%
“…Similar doses to the ones used in this study, however, did not result in any abnormal findings on routine pathologic examinations in control mice (39). Because L-cycloserine inhibits the synthesis of sphingosine, it is important to select a treatment regimen that does not completely inhibit the production of sphingosine as it is a key component of cells.…”
Section: Bone Marrow Transplantation In Twitchersmentioning
confidence: 61%
See 2 more Smart Citations
“…While most of the experimental tests have been done with animal models of lysosomal storage diseases, in which glucosylceramidebased sphingolipids are stored, using inhibitors of glucosylceramide synthesis, this approach is not feasible for GLD because the disease does not involve impaired degradation of glucosylceramide-based sphingolipids. Instead, the use of cycloserine, which inhibits all sphingolipid synthesis, was suggested to treat twitcher mice in 1984 (59) and recent trials found it to be slightly effective (60,61). It should be noted that this approach cannot reverse the disease process unless mutant enzyme has residual activity or there is a minor metabolic bypass pathway.…”
Section: Examples Of Therapeutic Attemptsmentioning
confidence: 99%